If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 4a + -3 Reorder the terms: 13 = -3 + 4a Solving 13 = -3 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. 13 + -4a = -3 + 4a + -4a Combine like terms: 4a + -4a = 0 13 + -4a = -3 + 0 13 + -4a = -3 Add '-13' to each side of the equation. 13 + -13 + -4a = -3 + -13 Combine like terms: 13 + -13 = 0 0 + -4a = -3 + -13 -4a = -3 + -13 Combine like terms: -3 + -13 = -16 -4a = -16 Divide each side by '-4'. a = 4 Simplifying a = 4
| 18x+50=18x+38 | | 5-x(3)=27 | | X-3.9/2.2 | | 40/98=s/112 | | 11+x=320 | | 70=14*x/2 | | 106=7x-6 | | 45000x+-275000=0 | | (-3x+4y)-(2x-5y)= | | -7a+6=27 | | V=XRU | | d=4-3d | | 7a+6=27 | | -19x=-95 | | 6(4x+5)=3(x+3)+3 | | g(-8)=-1/2(-8)+9 | | 4(8-6x)-6=-8x-34 | | -15/1/3d | | -3(n-2)=-2n-1 | | x+(-5)=1 | | -15/13/d | | 5(2x+7)=21-(4x+7) | | x^2+5x+4=X^2+56 | | 7x^(2/3)-48x^(1/3)-7=0 | | Dx-7c=x | | 2+8i^2= | | 4x+x+9=10x-5x+9 | | .2(g-6)=.6(g-4) | | (3d+2c)-(5d-4c)= | | 1/3(15x-9) | | 2(x-3)=9x-7-7x | | -6=4/7x |